The Social Construction and Use of Landscape and Public Space in the Age of Migration. Arab Immigrants in Berlin. - Al-Khanbashi, Mohammed (Springer VS, 2020)
With the rare researches that focus on the cross-cultural aspects, this book tends to investigate how Arab immigrants construct and use landscape and public space in Berlin as a host city. The approach of social constructivist landscape research is chosen to highlight the effects of past and present in their experiences, including the effect of home and childhood period, social and cultural background, previous and current migration experiences including the level of integration and patterns of settlements, the importance of networking including the sense of community and groups and shared interests, as well as place attachment, and hybridization. Biographical semi-structured interviews with 72 Arab immigrants in Berlin were conducted, in addition to both participant and site observation.
Keywords: Einwanderer; Immigration; Migration; Öffentlicher Raum; Urbaner Raum; Raumwahrnehmung; Nutzungsart; Alltagsverhalten; Integration; Aufenthaltsbereich; Halböffentlicher Raum; Freiraumnutzung; Freizeitaktivität; Stadtsoziologie; Stadtgeographie; Empirische Untersuchung; Interview; Araber